PROFIL STATUS GIZI DAN KOMPOSISI TUBUH REMAJA SANTRIWATI BERDASARKAN JENIS KEBIASAAN PUASA - Dieny, Fillah Fithra; Nur Aini, Fadhilah; Fauzia, Ria; Pramono, Adriyan; Susilo, Mursid Tri; Widyastuti, Nurmasari; Wijayanti, Lilis; Wijayanti, Hartanti Sandi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Female students in Islamic boarding school are one of the vulnerable groups to experience nutritional problems caused by several factors, one of which is because there are traditions that can change eating patterns. Changes in eating patterns can be caused by fasting traditions, such as Daud and Ngrowot. Objectives: This study aims to analyze the differences in nutritional status and body composition among female students based on type of fasting habits. This research is an observational analytical study with a cross sectional design at API Asri Syubbanul Wathon Islamic Boarding School Tegalrejo, Magelang in female students aged 16-18 years who were selected using stratified random sampling techniques. Subjects were divided into the Daud (n=34), Ngrowot (n=30), Daud and Ngrowot (33), and without Daud Ngrowot (n=31) groups. Data were analyzed using One-Way ANOVA and Kruskall-Wallis test. Most subjects had been fasting for 3 years and the majority of subjects who practiced Daud and Daud Ngrowot fasting rarely did sahur. However, the eating habits of the four groups did not different significantly. The majority of subjects eating twice a day and rarely exercising. Most of the subjects in the four groups had normal nutritional status, muscle mass, and body water percentage, but most subjects had above normal body fat percentage. There was no difference in nutritional status based on BMI/A (p=0.707), MUAC (p=0.594), WC (p=0.372), and WHR (p=0.201) and body composition such as body fat percentage (p=0.393), muscle mass (p=0.403), and total body water percentage (p=0.346) in the four groups. Nutritional status based on BMI/A, MUAC, WC, WHR, body fat percentage, muscle mass, and total body water percentage did not differ significantly between Daud, Ngrowot, Daud with Ngrowot, and without Daud Ngrowot groups.